Human CD40 ligand deficiency dysregulates the macrophage transcriptome causing functional defects that are improved by exogenous IFN-γ - Cabral-Marques, Otavio; Ramos, Rodrigo Nalio; Schimke, Lena F.; Khan, Taj Ali; Amaral, Eduardo Pinheiro; Barbosa Bomfim, Caio César; Junior, Osvaldo Reis; França, Tabata Takahashi; Arslanian, Christina; Carola Correia Lima, Joanna Darck; Weber, Cristina Worm; Ferreira, Janaíra Fernandes; et al. (Journal of allergy and clinical immunology, 2017)
CD40 ligand (CD40L) deficiency predisposes to opportunistic infections, including those caused by fungi and intracellular bacteria. Studies of CD40L-deficient patients reveal the critical role of CD40L-CD40 interaction for the function of T, B, and dendritic cells. However, the consequences of CD40L deficiency on macrophage function remain to be investigated. We sought to determine the effect of CD40L absence on monocyte-derived macrophage responses. After observing the improvement of refractory disseminated mycobacterial infection in a CD40L-deficient patient by recombinant human IFN-γ (rhIFN-γ) adjuvant therapy, we investigated macrophage functions from CD40L-deficient patients. We analyzed the killing activity, oxidative burst, cytokine production, and in vitro effects of rhIFN-γ and soluble CD40 ligand (sCD40L) treatment on macrophages. In addition, the effect of CD40L absence on the macrophage transcriptome before and after rhIFN-γ treatment was studied. Macrophages from CD40L-deficient patients exhibited defective fungicidal activity and reduced oxidative burst, both of which improved in the presence of rhIFN-γ but not sCD40L. In contrast, rhIFN-γ and sCD40L ameliorate impaired production of inflammatory cytokines. Furthermore, rhIFN-γ reversed defective control of Mycobacterium tuberculosis proliferation by patients' macrophages. The absence of CD40L dysregulated the macrophage transcriptome, which was improved by rhIFN-γ. Additionally, rhIFN-γ increased expression levels of pattern recognition receptors, such as Toll-like receptors 1 and 2, dectin 1, and dendritic cell–specific intercellular adhesion molecule 3–grabbing nonintegrin in macrophages from both control subjects and patients. Absence of CD40L impairs macrophage development and function. In addition, the improvement of macrophage immune responses by IFN-γ suggests this cytokine as a potential therapeutic option for patients with CD40L deficiency.